Răspuns :
[tex](3 - \sqrt{3} )(3 + \sqrt{3} ) = {3}^{2} - {( \sqrt{3} )}^{2} = 9 - 3 = 6[/tex]
[tex]Formul\check{a}\::(a - b)(a + b) = {a}^{2} - {b}^{2} [/tex]
[tex](2\sqrt{3}-5)(2\sqrt{3}+5)={(2\sqrt{3})}^{2}-{5}^{2}[/tex]
[tex]={2}^{2}\times3-25[/tex]
[tex]=4\times3-25[/tex]
[tex]=12-25[/tex]
[tex]=-13[/tex]
[tex]Formul\check{a}\::\:(a-b)(a+b)={a}^{2}-{b}^{2}[/tex]
[tex](x+1)(x+4)=x \times x+x \times 4+1\times x+1\times4[/tex]
[tex]={x}^{2}+4x+x+4[/tex]
[tex]={x}^{2}+5x+4[/tex]
[tex](x-6)(2x-5)=x\times2x+x\times(-5)-6\times2x-6\times(-5)[/tex]
[tex]=2{x}^{2}-5x-12x+30[/tex]
[tex]=2{x}^{2}-17x+30[/tex]
[tex]Formul\check{a}\::(a - b)(a + b) = {a}^{2} - {b}^{2} [/tex]
[tex](2\sqrt{3}-5)(2\sqrt{3}+5)={(2\sqrt{3})}^{2}-{5}^{2}[/tex]
[tex]={2}^{2}\times3-25[/tex]
[tex]=4\times3-25[/tex]
[tex]=12-25[/tex]
[tex]=-13[/tex]
[tex]Formul\check{a}\::\:(a-b)(a+b)={a}^{2}-{b}^{2}[/tex]
[tex](x+1)(x+4)=x \times x+x \times 4+1\times x+1\times4[/tex]
[tex]={x}^{2}+4x+x+4[/tex]
[tex]={x}^{2}+5x+4[/tex]
[tex](x-6)(2x-5)=x\times2x+x\times(-5)-6\times2x-6\times(-5)[/tex]
[tex]=2{x}^{2}-5x-12x+30[/tex]
[tex]=2{x}^{2}-17x+30[/tex]